(3GdLQYI GdUGajI hGdfaMI GdcGajIs - (3CHh Rjf GdYGHOjf GdhGaj , CHh Rjf GdYGHOjf Hf GdeNJGQ Hf CMeO Hf CHj HcQ GdcfJj,J (B1207 (3g` s
(3ChdgG (B:s
(3hGdMeO ddg dGPi LYd bdhH ChdjGFg hjfHhYkG ddYdhe GdXGgQI hGdMbGFb GdNajGJ s
(3BNQgG (B:s
,(3GdUMjM GdPi Ydjg GdCcKQhf Cfg ecQQI dCfg efTYGQ Cgd GdCghGA hGdHOY (B,(3ebOGQI GdYXje s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B198s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs